Valence electronic structure of [EMIM][BF4] ionic liquid: photoemission and DFT plus D study - Kuusik I; Berholts M; Kruusma J; Kisand V; Tonisoo A; Lust E; Nommiste E (ROYAL SOC CHEMISTRY, 2022)
The ultraviolet photoelectron spectrum (UPS) of the [EMIM][BF4] ionic liquid was recorded and analyzed. Together with the gas-phase UPS spectrum of the [EMIM][BF4] vapor and ab initio calculation methods, detailed insight into the electronic structure of this simple ionic liquid is possible. The low binding energy tail in the UPS spectrum is about 7.4 eV, in agreement with previous estimations of the HOMO-LUMO gap of the [EMIM][BF4] ion-pair. The bulk ab initio calculations are able to explain most of the features in the spectrum. However, DFT consistently lacks accuracy in the description of the top of the valence band. The dispersion corrected PBE calculation (PBE-D3) did offer very good agreement with the experimental structure, but the recently-developed vdW-DF functionals C09, optPBE, optB88 and CX were found to offer the best agreement in terms of the electronic structure.